2014
DOI: 10.1016/j.heares.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The auditory corticocollicular system: Molecular and circuit-level considerations

Abstract: We live in a world imbued with a rich mixture of complex sounds. Successful acoustic communication requires the ability to extract meaning from those sounds, even when degraded. One strategy used by the auditory system is to harness high-level contextual cues to modulate the perception of incoming sounds. An ideal substrate for this process is the massive set of top-down projections emanating from virtually every level of the auditory system. In this review, we provide a molecular and circuit-level description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 97 publications
(157 reference statements)
4
80
0
Order By: Relevance
“…Chernock et al (2004) reported previously that modules positive for GAD-67, PV, AChE, CO, and NADPH-d are present in the rat, but are absent in mouse, squirrel, cat, bat, macaque monkey, and barn owl. However, images of mouse tissue from other sources depict modular staining patterns in the LC for GAD-67, AChE, NADPH-d, and CO (Gonzalez-Lima and Cada, 1994;Paxinos and Franklin, 2004;Ono et al, 2005;Stebbings et al, 2014;Choy Buentello et al, 2015). In addition, images of stained tissue from other species reveal modules in the LC of the gerbil and the rhesus macaque (Paxinos et al, 1999;Cant and Benson, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chernock et al (2004) reported previously that modules positive for GAD-67, PV, AChE, CO, and NADPH-d are present in the rat, but are absent in mouse, squirrel, cat, bat, macaque monkey, and barn owl. However, images of mouse tissue from other sources depict modular staining patterns in the LC for GAD-67, AChE, NADPH-d, and CO (Gonzalez-Lima and Cada, 1994;Paxinos and Franklin, 2004;Ono et al, 2005;Stebbings et al, 2014;Choy Buentello et al, 2015). In addition, images of stained tissue from other species reveal modules in the LC of the gerbil and the rhesus macaque (Paxinos et al, 1999;Cant and Benson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The LC also receives top-down information from the superior colliculus (SC) and the somatosensory, auditory, and visual cortices (Cooper and Young, 1976;Robards, 1979;Adams, 1980;Faye-Lund, 1985;Winer et al, 1998). Previous studies that have mapped the terminal distributions of these pathways show that many of them form discontinuous patches within the LC in a number of species, including the mouse, guinea pig, cat, and monkey (Wise and Jones, 1977;Wiberg and Blomqvist, 1984;Faye-Lund and Osen, 1985;Wiberg et al, 1987;Saldaña and Merchań , 1992;Saldaña et al, 1996;Zhou and Shore, 2006;Stebbings et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferior colliculus (IC) forms a major convergence region within the auditory system, as it receives feed-forward projections from the auditory brainstem (Oliver, 1984(Oliver, , 1987Glendenning et al, 1992;Saint Marie et al, 1997), feedback projections from the auditory cortex (Winer et al, 1998;Winer, 2006;Stebbings et al, 2014 for a comprehensive review), and commissural connections from contralateral structures (Aitkin and Phillips, 1984). In turn, the IC sends descending fibres to a variety of brainstem nuclei (Huffman and Henson, 1990), and ascending projections to the auditory thalamus (Andersen et al, 1980).…”
Section: Inferior Colliculusmentioning
confidence: 99%
“…These structures generate multiple feedback loops that extract meaning from afferent stimulation through modulation 14,15 . Cortical stimulation affects the tuning curves of subcortical structures causing specific regions in the subcortical system to become robustly tuned to higher levels of activity [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%